2020
DOI: 10.1016/j.ijcard.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K antagonist oral anticoagulants (NOACs) for thromboembolic prevention, are they safe in congenital heart disease? Results of a worldwide study

Abstract: Background: Current guidelines consider vitamin K antagonists (VKA) the oral anticoagulant agents of choice in adults with atrial arrhythmias (AA) and moderate or complex forms of congenital heart disease, significant valvular lesions, or bioprosthetic valves, pending safety data on non-VKA oral anticoagulants (NOACs). Therefore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 33 publications
1
47
2
4
Order By: Relevance
“…Yang et al [ 28 ] reported on the results of the NOTE registry, the first international multicenter cohort study assessing the safety and efficacy of NOACs (rivaroxaban 43%; apixaban 39%; dabigatran 12%; edoxaban 7%) in ACHD patients. A quarter of patients (28%, n = 150) were previously on Vitamin K Antagonist (VKA) therapy and served as historic controls.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [ 28 ] reported on the results of the NOTE registry, the first international multicenter cohort study assessing the safety and efficacy of NOACs (rivaroxaban 43%; apixaban 39%; dabigatran 12%; edoxaban 7%) in ACHD patients. A quarter of patients (28%, n = 150) were previously on Vitamin K Antagonist (VKA) therapy and served as historic controls.…”
Section: Resultsmentioning
confidence: 99%
“… 33 34 The independent endpoint adjudication of PROTECT-AR will allow for comprehensive, quality details on the endpoints of interest, in compliance with predefined standards. In a similar fashion to the NOTE (NOACs for thromboembolic prevention in patients with CHD) study, 10 PROTECT-AR exploits an existing pool of phenotypically characterised patients with ACHD, nested into active, local ACHD-all-comers registries, from which ongoing apixaban users are to be selected. Such use of already available resources is expected to offer several advantages compared with other studies: First, it will reduce time and recruitment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet even after a decade on the market, most data generated by studies on ACHD patients with AA focused on NOACs in general, rather than apixaban per se. [7][8][9][10] To address this gap in knowledge, we designed the PReventiOn of ThromboEmbolism in Adults with Congenital HearΤ disease and Atrial aRrhythmias (PROTECT-AR) trial. The trial aims to evaluate the safety and efficacy of apixaban use for thromboembolism prevention, in routine, 'real-world' practice regarding ACHD patients with AA.…”
Section: Introductionmentioning
confidence: 99%
“…Our national registry (CONCOR) and international networks such as the ISACHD and the EuroGUCH facilitate worldwide collaborative ACHD research and education. Several international initiatives have been undertaken to improve efficacy, such as the NOTE Registry, a global study assessing the efficacy and safety of non-vitamin K oral antagonists in preventing thromboembolic complications in ACHD and the ROPAC study, describing the outcome of pregnancy in cardiac patients, including ACHD [ 38 , 39 ]. Much of this research is integrated in the 2020 European Cardiac Society guideline on adult CHD.…”
Section: Clinical Researchmentioning
confidence: 99%